HOME, SCHOOL AND STUDENTS’ CHARACTERISTICS AS PREDICTORS OF SENIOR SECONDARY SCHOOL STUDENTS’ ACHIEVEMENT IN MATHEMATICS - Okunola, Joseph Oluwasegun; Obot, Patrick Friday (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Students’ performance in mathematics in Nigeria in recent times is not at a desired level. Despite relentless efforts by stakeholders to improve on this situation, yet no significant change. Studies that looked into student’s variables combined with importance of mathematics, teacher, school, and parent variables to predict students’ achievement in mathematics, seem not to be in existence. Thus, empirical documentation of such is needful. This study assessed home, school and students’ characteristics as predictors of Senior Secondary School students’ achievement in Mathematics in Osun State. Expo-facto design of non-experimental type was used. Descriptive statistics and Multiple Regression were used to analyze data at 0.05 alpha level. Results reveal that parenting type, family size, teachers qualification, years of teaching, class size, interest in mathematics, student academic engagement, and importance of mathematics, jointly accounted for 11% of observed variance in achievement in Mathematics, and it is statistically significant, F(17,575) = 5.183; P < 0.05. Also, importance of mathematics, student engagement, teachers qualification, class size and teacher years of teaching, were found to have significant relative contribution towards students’ achievement in mathematics, and they could reliably predict achievement in mathematics.